2002
DOI: 10.1007/s00468-002-0166-6
|View full text |Cite
|
Sign up to set email alerts
|

Early growth of seven mangrove species planted at different elevations in a Thai estuary

Abstract: This study aimed to determine the effect of elevation on survival and growth of mangrove seedlings during the establishment period. Seven typical mangrove species, Rhizophora mucronata Poir, R. apiculata Bl., Bruguiera cylindrica (L.) Bl., Ceriops tagal (Pirr.) C.B. Rob., Sonneratia alba J. Sm., Avicennia officinalis L. and Xylocarpus granatum Koenig were planted at various topographic sites in an intertidal zone of Phang Nga province, southern Thailand. These six bare areas included two that were abandoned af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 6 publications
1
33
0
Order By: Relevance
“…Prior to seedling establishment, processes such as dispersal towards the concerning shrimp farm areas and propagule predation are likely to influence initial patterns of distribution and abundance (Cannicci et al, 2008;Dahdouh-Guebas et al, 1997, 1998McGuinness, 1994;McKee, 1995;Osborne and Smith, 1990). Once arrived in the abandoned shrimp farms, other factors like physico-chemical characteristics of the sediment (Delgado et al, 2001), predation (Cannicci et al, 2008), acid sulphate soils (Sammut and Hanafi, 2000), interspecific competition and frequency of inundation (Kitaya et al, 2002) may further affect the success of establishment, early growth and survival of seedlings and ultimately determine the success of natural regeneration.…”
Section: Implications Of Propagule Dispersal For Shrimp Pond Rehabilimentioning
confidence: 99%
“…Prior to seedling establishment, processes such as dispersal towards the concerning shrimp farm areas and propagule predation are likely to influence initial patterns of distribution and abundance (Cannicci et al, 2008;Dahdouh-Guebas et al, 1997, 1998McGuinness, 1994;McKee, 1995;Osborne and Smith, 1990). Once arrived in the abandoned shrimp farms, other factors like physico-chemical characteristics of the sediment (Delgado et al, 2001), predation (Cannicci et al, 2008), acid sulphate soils (Sammut and Hanafi, 2000), interspecific competition and frequency of inundation (Kitaya et al, 2002) may further affect the success of establishment, early growth and survival of seedlings and ultimately determine the success of natural regeneration.…”
Section: Implications Of Propagule Dispersal For Shrimp Pond Rehabilimentioning
confidence: 99%
“…These topographic characteristics play an important role in the patterns of mangrove development and maintenance. Substrate elevation and topographical variations have been recognized as important criteria in the success and patterns of mangrove seedling establishment (Anthony 2004, Ellison 1998, Kitaya et al 2002, Saenger 2003, Cohen et al 2005, Lara and Cohen 2006. Both topography and plant distribution serve as a pattern for the accumulation of organic matter (such as hydrocarbons) and inorganic (such as metals) species.…”
Section: Discussionmentioning
confidence: 99%
“…Seedling mortality as function of elevation Kitaya et al (2002) measured seedling survival for seven different mangrove species on different elevations on the tidal flat. Their findings indicated that mortality rates are both strongly dependent on elevation and are species specific.…”
Section: Local Feedbacksmentioning
confidence: 99%
“…Their findings indicated that mortality rates are both strongly dependent on elevation and are species specific. Kitaya et al (2002) did not, however, measure seedling survival for A. marina. We therefore assume that the relation between mortality and elevation can be described using a Hill-like function:…”
Section: Local Feedbacksmentioning
confidence: 99%
See 1 more Smart Citation